2024
DOI: 10.1002/2056-4538.12363
|View full text |Cite
|
Sign up to set email alerts
|

Verification of molecular subtyping of bladder cancer in the GUSTO clinical trial

Jon Griffin,
Jenny Down,
Lewis A Quayle
et al.

Abstract: The GUSTO clinical trial (Gene expression subtypes of Urothelial carcinoma: Stratified Treatment and Oncological outcomes) uses molecular subtypes to guide neoadjuvant therapies in participants with muscle‐invasive bladder cancer (MIBC). Before commencing the GUSTO trial, we needed to determine the reliability of a commercial subtyping platform (Decipher Bladder; Veracyte) when performed in an external trial laboratory as this has not been done previously. Here, we report our pre‐trial verification of the TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…While some studies have shown that molecular subtypes could be potentially used to personalize BC treatment 17,21 , we achieved poor AUCs for RF models using the LundTax and TCGAclas subtypes (0.41 and 0.51, respectively; Supplementary Fig. 5D, Supplementary Table 10).…”
Section: Figure 5: Machine Learning Models With Rna-seq and Wes Data ...mentioning
confidence: 77%
See 1 more Smart Citation
“…While some studies have shown that molecular subtypes could be potentially used to personalize BC treatment 17,21 , we achieved poor AUCs for RF models using the LundTax and TCGAclas subtypes (0.41 and 0.51, respectively; Supplementary Fig. 5D, Supplementary Table 10).…”
Section: Figure 5: Machine Learning Models With Rna-seq and Wes Data ...mentioning
confidence: 77%
“…Some studies suggest that MIBC molecular subtypes predict NAC response, and can be useful for treatment selection and improving outcomes 17 . However, these findings have been demonstrated to be inconsistent over time.…”
Section: Introductionmentioning
confidence: 99%